HUBUNGAN PERKEMBANGAN SOSIAL EMOSIONAL TERHADAP KEMANDIRIAN ANAK USIA DINI DI TK UMMUL HABIBAH DESA KELAMBIR V MEDAN - Munisa (Jurnal Abdi Ilmu, 2019)
The research aims to determine the emotional social development relationship to early childhood independence. Children are not yet social and children have no ability to associate with others. To achieve social maturity, the child must learn about ways to adapt to others. The importance of habituation of the emotional social value of children early on in terms of self-reliance. Social development is the level of child interaction with others, ranging from parents, relatives, friends to play, to the community broadly. While emotional development is an overflow of feeling when the child interacts with others. Some children still depend on their parents to solve problems both at school and at home. This certainly affects the social ability and independence level of early childhood. Emotional social habituation for early childhood is essential to be applied as early as possible so that the child is able to solve the problem and make decisions without relying on others. This greatly affects the child's independence.